Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1103/physrevc.80.032501
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the double-βdecay half-life ofNd150and search for neutrinoless decay modes with the NEMO-3 detector

Abstract: The half-life for double beta decay of 150 Nd has been measured by the NEMO-3 experiment at the Modane Underground Laboratory. Using 924.7 days of data recorded with 36.55 g of 150 Nd the half-life for 2νββ decay is measured to be T 2ν 1/2 = (9.11 +0.25 −0.22 (stat.) ± 0.63 (syst.)) × 10 18 years. The observed limit on the half-life for neutrinoless double beta decay is found to be T 0ν 1/2 > 1.8×10 22 years at 90% Confidence Level. This translates into a limit on the effective Majorana neutrino mass of mν < 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 18 publications
0
56
0
Order By: Relevance
“…The latter value agrees well with the experimental value of 0.0579 ± 0.0032; this value is obtained from the average of three experimental half-lives [64] (for the experiments, see Refs. [65][66][67]) and the phase-space factor in Ref. [16].…”
Section: B Nuclear Matrix Element Of 2νββ Decaymentioning
confidence: 99%
“…The latter value agrees well with the experimental value of 0.0579 ± 0.0032; this value is obtained from the average of three experimental half-lives [64] (for the experiments, see Refs. [65][66][67]) and the phase-space factor in Ref. [16].…”
Section: B Nuclear Matrix Element Of 2νββ Decaymentioning
confidence: 99%
“…The total mass of the enriched ZrO 2 is 22.0 g of which 9.4 ± 0.2 g is 96 Zr [7]. NEMO-3 results thus far are published in [8,9,10,11].…”
Section: Nemo-3 Experimental Apparatusmentioning
confidence: 99%
“…The difference never exceeds 5% for the internal backgrounds, therefore the uncertainty on the 2νββ half-life is estimated by fluctuating the internal backgrounds ± 5% and recording the corresponding change in 2νββ half-life. The world's best 2νββ half-life measurements for 150 Nd [21,11] and 48 Ca [22] have been recently obtained. These isotopes neighbor the 96 Zr source and are included as backgrounds.…”
Section: The Systematic Errormentioning
confidence: 99%
“…As a result, it is concluded that the new long-range mode induced by O 7 gives the dominant contribution to the 0νββ decays in the present scenario. By comparing the current experimental limits on the 0νββ half-life of different nuclei [64][65][66][67][68][69][70], we can actually give the strong constraints to the Wilson coefficient C ud ee by assuming Λ ∼ 1 TeV. The numerical limits are collected in table 1, from which it is seen that the strongest constraint is given by the target 136 Xe [65,66] with |C ud ee | < 1.9 × 10 −4 .…”
Section: Jhep03(2017)103mentioning
confidence: 99%